Sosialisasi Peran Aparat Desa Buncitan dalam Penyelenggaraan Penataan Ruang Sidoarjo - Linda Dwi Rohmadiani; Suning Suning; Anak Agung Sagung Alit Widyastuty; Moch Shofwan; Siti Nuurlaily Rukmana; Annisa Budhiyani Tribhuwaneswari (Damhil: Jurnal Pengabdian kepada Masyarakat, 2023)
Buncitan village has an area of 145.9 hectares with a population of 4,976 people and 1,981 households. The function and role of Sedati Sub-district according to Sidoarjo Regency Regional Regulation No. 9 of 2009 concerning the Regional Spatial Plan of Sidoarjo Regency 2009-2029 is as a settlement, industry and trade on a local, regional and international scale. The issuance of the Job Creation Law and Government Regulation on the Implementation of Spatial Planning that changes the authority of local governments in district or city spatial planning needs to be socialized to village officials, so that they are expected to increase their participation in supporting spatial planning. The method of implementing the activity uses a socialization method that begins with distributing a pre-test and ends with a post-test regarding understanding in the implementation of spatial planning. The results obtained were the initial condition of the level of understanding of village officials about their role in the implementation of spatial planning of 78% while post-socialization increased to 100%. The findings of community service that can be input for the local government are the need for socialization and ease of accessing the district spatial plan regional regulation document for the Buncitan Village community.